Tβ4 Increases Neovascularization and Cardiac Function in Chronic Myocardial Ischemia of Normo- and Hypercholesterolemic Pigs - Ziegler, Tilman; Baehr, Andrea; Howe, Andrea; Klett, Katharina; Husada, Wira; Weber, Christian; Laugwitz, Karl-Ludwig; Kupatt, Christian; Hinkel, Rabea (Molecular Therapy, 2018)
Cardiovascular risk factors, such as hypercholesterolemia, impair cardiac function in chronic ischemia. Ziegler et al. demonstrate that cardiac transduction of thymosin β4 is capable of inducing therapeutic neovascularization and, thereby, improving cardiac function in a translational large animal model with cardiovascular risk factor.
CRIS-Team Scopus Importer:2023-03-08
Keywords: adeno-associated viral vectors; cardiovascular risk factors; gene therapy; hypercholesterolemia; myocardial ischemia; therapeutic neovascularization; thymosin β4